ТЕАТР ТАРИЙХЫ ҲӘМ ОНЫҢ РАЎАЖЛАНЫЎ БАСҚЫШЛАРЫ (ART AND CULTURE BULLETIN, 2026)
This article analyzes the emergence of theatrical art, its historical development, and its stagesof development across different periods. Furthermore, the role and importance of the theatre in social lifehave been scientifically explored
Keywords: theatre; dramaturgy; stage art; ancient theatre; tragedy; comedy; directing; acting.